1981
DOI: 10.1007/bf00779387
|View full text |Cite
|
Sign up to set email alerts
|

The needs of prisoners' wives: A challenge for the mental health professions

Abstract: This research assessed the needs of prisoners' wives in six areas (information, finances, relationships with friends, family relationships, grief, and relationships with children) and determined if stage of separation or previous experience with the correctional system affected those needs. High levels of need were found in each area. Women in the initial stage of separation had significantly greater need for information than women in the pre-reunion stage, but prior experience with the correctional system did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…Using these variables, Morris constructed a typology with eight situations predicting whether marital relationships would be strained or strengthened by a husband's imprisonment, and she made specific recommendations for the "treatment of family problems as a whole" by prison and social services (Morris 1965, p. 10). Yet rather than inspiring derived studies, development of her analytical framework, or implementation of her suggested policy reforms, Morris's substantial contribution lay essentially untouched by the sparse and conceptually isolated publications of the next three decades, which appeared chiefly in psychology, social work, criminology, and corrections (see, for example, Gibbs 1971, Sack et al 1976, Bakker et al 1978, Daniel & Barrett 1981, Goetting 1982, Hinds 1982, Hannon et al 1984, Lowenstein 1986.…”
Section: Introductionmentioning
confidence: 98%
“…Using these variables, Morris constructed a typology with eight situations predicting whether marital relationships would be strained or strengthened by a husband's imprisonment, and she made specific recommendations for the "treatment of family problems as a whole" by prison and social services (Morris 1965, p. 10). Yet rather than inspiring derived studies, development of her analytical framework, or implementation of her suggested policy reforms, Morris's substantial contribution lay essentially untouched by the sparse and conceptually isolated publications of the next three decades, which appeared chiefly in psychology, social work, criminology, and corrections (see, for example, Gibbs 1971, Sack et al 1976, Bakker et al 1978, Daniel & Barrett 1981, Goetting 1982, Hinds 1982, Hannon et al 1984, Lowenstein 1986.…”
Section: Introductionmentioning
confidence: 98%
“…Maintaining contact with an inmate, however, is also stressful, costly and potentially stigmatizing for the family and other visitors (Hairston, 1991). While the psychological costs and stigma of imprisonment of a family member and of prison visiting has been well-documented (Girshick, 1996;Daniel and Barrett, 1981;Moerings, 1992;Fishman, 1988a), and the financial burdens of visiting and maintaining contact with an incarcerated person have been described qualitatively (Girshick, 1996), the actual financial costs have not been assessed quantitatively.…”
Section: Introductionmentioning
confidence: 98%
“…However, none of them have specifically investigated the experiences of women being separated from their husbands as a result of political imprisonment (The Ministry of Detainees and Ex-Detainees Affairs 2012: Baker 2011, p. 101). Other studies did investigate the influence of having husbands arrested but for criminal reasons (Arditti et al 2003;Codd 2007;Daniel and Barrett 1981;Fishman 1990;Hairston 1998;Lenora Madison 1992;Miller 2006;Pfiffner et al 2001;Robin and Lisa 2001;Travis 2005;Wildeman et al 2012). Several studies have found that the availability of social support is essential for the wellbeing of individuals in stressful situations (Agani 2001;Ahern et al 2004;Bültmann et al 2002;Cohen and Wills 1985;Olstad et al 2001;Taylor et al 2004).…”
Section: Introductionmentioning
confidence: 95%